Design Optimization of a Dual-band Microstrip SIW Antenna using Differential Evolutionary Algorithm for X and K-Band Radar Applications - Belen, Aysu; Gunes, Filiz; Mahouti, Peyman (APPLIED COMPUTATIONAL ELECTROMAGNETICS SOC, 2020)
In this work, design optimization and fabrication of a high performance microstrip dual-band antenna are presented using Substrate Integrated Waveguide (SIW) technology with Roger 4350 (epsilon(r)=3.48 and h=1.52mm). Firstly, the SIW antenna design is considered as a multi-objective multi-dimensional optimization problem for a simple microstrip geometry and its geometrical parameters are optimized efficiently using Differential Evolutionary Algorithm (DEA) in the 3D CST Microwave studio environment based on the gain and return loss characteristics at 12 GHz and 24 GHz. In the second step, for justification of the proposed design method, the optimally designed dual band microstrip SIW antenna has been prototyped. Furthermore, the experimental results are compared with the performance measures of other counterpart designs in literature. Thus, based on the obtained results and comparisons, it can be concluded that the proposed microstrip SIW antenna model and its optimization procedure, is a sufficient and low-cost solution for X and K band radar applications.
Keywords: dual band; microstrip; optimization; substrate integrated waveguide; Differential evolutionary algorithm; Engineering; Telecommunications